ENHANCING LOAN ORIGINATION THROUGH DIGITIZATION AND DATA ANALYTICS IN BANK BRI - Setyarko, Ardhy; Nugraha, Erik Ridha; Wibawa, Tio Anta; Dewi, Nurma Gupita (Universitas YPPI Rembang, 2024)
Digitalization and data analytics in loan origination offer numerous benefits to banking institutions, including increased processing speed, improved decision-making, cost efficiencies, better customer experiences, and easier regulatory compliance. However, these advancements come with challenges such as cybersecurity risks, high initial costs, privacy concerns, technology adaptation difficulties, and system integration complexities. By implementing appropriate solutions, such as improving cybersecurity, conducting financial analyses, ensuring transparent data use, providing training, and seeking expert assistance, banks can address these limitations and fully leverage the benefits of enhanced loan origination efficiency. The adoption of digitalization and data analytics has transformed traditional loan origination processes into streamlined and efficient systems. Digitalization has enabled banks to automate workflows, reduce processing times, and improve customer experiences. Data analytics has provided banks with insights into customer behavior, credit risk, and fraud detection